Scalable video coding : a review - Maarif, Haris Al Qodri; Gunawan, Teddy Surya; Khalifa, Othman Omran (IIUM Press, 2011)
Scalable video coding (SVC) is classified as layered video codec which is the extension of H.264/AVC standard [I, 2]. SVC based layered video coding is suitable for different usecases and different bitstream e.g., supporting heterogeneous devices with a single, scalable bitstream. Such a stream allows for delivering a decode-able and presentable quality of the video depending on the device capabilities. In terms of spatiotemporal and quality, scalability of SVC is referred as a functionality that allows the removal of par1s of the bit-stream while achieving a reasonable coding efficiency of the decoded video at reduced temporal, Signal to Noise Ratio (SNR), or spatial resolution [3]. The three different types of scalability, i.e. CGS, MGS, and FGS, can be combined in order that the single scalable bitstream can support multitude of representations with different spatiotemporal resolutions and bit rates. The efficient scalable video coding provides benefits in many applications [3-5].